2018
DOI: 10.1093/ndt/gfy313
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of peritoneal transport characteristics in dialysis patients with ultrafiltration failure: tissue and capillary components

Abstract: Background Ultrafiltration failure (UFF) in peritoneal dialysis (PD) patients is due to altered peritoneal transport properties leading to reduced capacity to remove excess water. Here, with the aim to establish the role of local alterations of the two major transport barriers, peritoneal tissue and capillary wall, we investigate changes in overall peritoneal transport characteristics in UFF patients in relation to corresponding local alterations of peritoneal tissue and capillary wall transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 30 publications
(41 reference statements)
2
38
0
Order By: Relevance
“…Although the relative abundance of primarily IgG-derived glycans was not associated with several inflammation markers or PET-creatinine and PET-UF, no such association was tested for the abundance of pro-inflammatory, agalactosylated glycated IgG. In keeping with the relevance of preserving residual kidney function in maintaining euvolemia and delaying the occurrence of UF failure, both highly correlated with PD patient survival [77][78][79], it would be of great interest to investigate if the decline of residual kidney function and UF failure correlates with the pro-inflammatory and anti-inflammatory IgG N-glycosylation pattern in both diabetic and non-diabetic PD patients.…”
Section: Peritoneal Ultrafiltration Failurementioning
confidence: 99%
“…Although the relative abundance of primarily IgG-derived glycans was not associated with several inflammation markers or PET-creatinine and PET-UF, no such association was tested for the abundance of pro-inflammatory, agalactosylated glycated IgG. In keeping with the relevance of preserving residual kidney function in maintaining euvolemia and delaying the occurrence of UF failure, both highly correlated with PD patient survival [77][78][79], it would be of great interest to investigate if the decline of residual kidney function and UF failure correlates with the pro-inflammatory and anti-inflammatory IgG N-glycosylation pattern in both diabetic and non-diabetic PD patients.…”
Section: Peritoneal Ultrafiltration Failurementioning
confidence: 99%
“…One may expect higher concentration of amylase in interstitial fluid than in dialysate so the osmolality of interstitial fluid may differ from that of dialysate. According to the distributed model, the sodium dip measured for glucose-based hypertonic fluids occurs also in the interstitial fluid, not only in dialysate, and this observation suggests the importance of the processes inside the tissue in contact with peritoneal dialysate (Stachowska-Pietka et al, 2012, 2019). The conjecture about the role of interstitium in the process of osmotic fluid transport induced by polyglucose is hypothetical and will need further theoretical, experimental, and clinical studies to be confirmed.…”
Section: Discussionmentioning
confidence: 92%
“…Previous study has demonstrated that an increase in the number of blood vessels in the peritoneal tissues of PD patients was commonly observed and more pronounced in those of PD patients with peritoneal membrane ultrafiltration failure 44 . Consistent with the previous study 44 , our study demonstrated a progressive increase in submesothelial thickening (i.e., through EMT process), in number of blood vessels and in a unique vasculopathy after CG-treated F344 PF.…”
Section: Discussionmentioning
confidence: 95%